Design of remover system for conveyor lines of food industry - A. M. Lasitsa; I. A. Borodikhin; P. A. Lisin; L. V. Brizhansky (Омский научный вестник)
The article shows that when designing a remover system for conveyor lines of the food industry it is necessary to consider all stages of the technological process. Thermodynamic calculations showing the effect of the degree of crystallization of water, cryoscopic temperature and crystallization rate are presented. The estimation of different methods for approximating temperature dependencies is given. A significant effect of the state of the surface on the separation force of remover is revealed. Recommendations on the setting technological parameters are given.